The relationship between functional movement patterns, dynamic balance and ice speed and agility in young elite male ice hockey players - Grabara,Małgorzata; Bieniec,Anna (PeerJ, 2024)
Background Understanding the relationship between the functional state of the musculoskeletal system and skating performance in ice hockey players is essential, as it can provide valuable insights for the development of training programs tailored to the specific needs of athletes. This study investigated the relationship between functional movement patterns, dynamic balance, and ice speed and agility in young elite male ice hockey players. Methods The study involved sixty elite male ice hockey players aged 14 to 18 years, with an average age of 15.9 ± 0.85 years and training experience ranging from 7 to 9 years. Functional movement patterns were evaluated using the Functional Movement Screen™ (FMSTM). Dynamic balance was assessed using the lower quarter Y-Balance test (YBT-LQ). Fitness tests on ice were conducted using a professional Smart Speed measurement system. Results Negative correlations were found between the in-line lunge and the results of the 5-m forward (rho = −0.31, p = 0.018) and 5-m backward (rho = −0.27, p = 0.040), as well as between the hurdle step and the 30-m forward skating test result (rho = −0.26, p = 0.043). Positive correlations were observed between shoulder mobility and both forward (5-m: rho = 0.27, p = 0.035) and backward skating results (5-m: rho = 0.35, p = 0.006; 30-m: rho = 0.26, p = 0.047), and between active straight leg rise and both the 5-m forward skating (rho = 0.38, p = 0.002) and agility tests (rho = 0.39, p = 0.002). The study also revealed positive correlations between the magnitude of asymmetries in the anterior reach distance of the right and left legs and the results of 5-m forward (rho = 0.34, p = 0.009) and backward skating (rho = 0.32, p = 0.013). Additionally, a positive correlation was found between the agility test and the magnitude of asymmetries in the posteromedial reach distance (r = 0.32, p = 0.012) as well as the composite YBT score (r = 0.28, p = 0.031). Negative correlations were found between normalized reach distances in the YBT-LQ and performance outcomes in both forward and backward skating, as well as in the agility test, indicating that greater reach distance corresponds to faster skating. Conclusions These findings suggest the potential impact of balance and hip mobility on skating speed and agility and emphasize the importance of symmetry for optimal performance among ice hockey players.
Keywords: Functional movement screen™; The lower quarter Y-balance test; Forward skating; Backward skating